Energy conversion - Amar Berkache (University of Msila, 2025)
In the context of increasing global energy demand and growing environmental concerns, a thorough understanding of energy conversion processes is essential for the development of efficient and sustainable energy systems. This book is designed to provide undergraduate students, particularly those specializing in Energy Engineering, with a solid foundation in the principles of applied thermodynamics relevant to modern energy technologies. The content is organized into four interconnected chapters that progressively address the fundamental aspects of energy systems. The first chapter examines single-phase thermodynamic cycles that underpin the operation of heat engines and gas-based power systems, including classical cycles such as Carnot, Otto, Diesel, Brayton, and Stirling, along with techniques for improving thermal efficiency. The second chapter focuses on two-phase cycles used in steam power generation, covering the Rankine cycle and its extensions, as well as hybrid energy systems, cogeneration, and an introduction to nuclear power systems. The third chapter introduces exergy analysis as an advanced thermodynamic tool for identifying energy losses and system inefficiencies, with practical applications to gas and steam power plants. Through a structured and pedagogical approach, this book aims to equip students with the theoretical knowledge and analytical tools necessary to understand, evaluate, and optimize energy conversion systems in a sustainable engineering context. The fourth and final chapter addresses the thermodynamics of combustion, a topic that underpins many energy systems based on chemical energy conversion. Students are introduced to the behavior of reactive gas mixtures, stoichiometric calculations, flame temperatures, and the principles of ignition, both spontaneous and controlled. The chapter also delves into chemical kinetics, examining reaction mechanisms and factors that influence combustion processes, such as pressure, temperature, and reaction rates. Overall, this coursebook is intended to reinforce the knowledge gained through lectures, tutorials, and practical laboratory sessions. It also serves as a reference guide for academic projects, research endeavors, and more advanced coursework in the field of energy engineering.
Keywords: Energy engineering; single-phase; thermodynamic cycles; two-phase cycles; concept of exergy; thermodynamics of combustion